Systematic review: characteristics of myocarditis followed by fixed drug eruption and dry eye syndrome in patients who have been vaccinated with monkeypox in children and adults - Mohamad Javier, R.; Prijanto, Stephanie Angela; Yora, Vallexa Septina; Yuliana Eka Pratiwi, Desak Gede; Lilhawa Ditsi, Errini Sabilla; Adelia, Bella; Tansuri, Verika Christabela; Wijaya, Hendry; Caecarma, Georaldhy Yussufy; Damayanti, Intan Trikumala; Ramadhanti, Anisa; Rahmaputri, Atika; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe Monkeypox Virus (MPOX) has caused a surge in viral infections, leading to the WHO recognizing it as a public health emergency of international concern. MPOX infection shares clinical similarities with smallpox but can cause complications like myocarditis, anorectal pain, ocular lesions, kidney damage, or soft tissue superinfection. The study aims to understand the characteristics of myocarditis, fixed drug eruption, and dry eye syndrome in Monkeypox patients.MethodsThis review was conducted based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), and the Cochrane Handbook for Systematic Reviews of Interventions. The data was obtained from Scopus and international journal databases by conducting combined keyword searches restricted to English-language publications.ResultThe study examined 25 cases of Monkeypox, primarily involving males aged 32.9 years and experiencing chest pain. The prognosis was generally good, with no reported death. Risk factors for infection include sexual activity, STD diagnosis, sexual encounters, and workplace exposure to orthopoxviruses. Most cases were male and involved chest pain. Myocarditis, an inflammation in the myocardium, can cause dilated cardiomyopathy, acute arrhythmia, and heart failure. The pathophysiology of myocarditis in Monkeypox patients is not yet determined due to rarity of cases.ConclusionMPOX infection presents unique complications like myocarditis, necessitating research for vaccines, antiviral drugs, and infection prevention measures. Early screening for chest pain and investigating MPXV infection's pathogenesis and clinical features are crucial for differential diagnosis during outbreaks. This systematic review can determine MPOX infection outcomes and prepare appropriate treatment for patients with complications.